Cartographic support for territorial development strategies: actuality, present state and perspectives - Попович, Н. В.; Пересадько, В. А. (Visnyk of V. N. Karazin Kharkiv National University. Series Geology. Geography. Ecology, 2018)
Formulation of the problem. The authors of the territorial development strategies actively use different means of data visualization (tables, graphs, diagrams, infographics), neglecting maps. For example, only 14 % of the national sustainable development strategies of European countries are provided with maps. The root of the problem is the lack of a basic concept as to creation of strategy maps.The purpose of the article is to substantiate the relevance of cartographic support for the territorial development strategies, analyze its current state and define prospects.Main results. Maps are not only vivid and comprehensive means of data visualization, but also material for spatial analysis of the quality in achieving objectives set in the strategies. We consider active use of maps in development strategies relevant for all countries with a high level of geographic literacy and rich cartographic traditions.The analysis of modern development strategies of various territorial levels (145 documents have been analyzed) allowed us to highlight the following trends in their cartographic support: prevalence of survey maps over thematic ones; dominance of inventory and evaluation analytical maps; schematic character and aesthetic appeal of maps.At different stages of strategic planning it is appropriate to use various types of maps: at preplanning stage - survey, physical-geographic, socio-economic, ecological maps; when defining goals and objectives - it is expedient to develop at least one map illustrating its contents for each of the objectives set; when choosing the optimal scenario for the territory development - it is recommended to develop forecast maps; at the stage of strategy implementation - it is necessary to reflect the dynamics of indicators set for the objectives.Conclusions. Creating maps for territorial strategies is a new direction in thematic mapping. Its perspective development requires active involvement of cartographers into the formation of strategies, use of modern cartographic works, in particular web-atlases, and creation of mapping methodology.